Structural behavior of piles under vehicular collision load on bridge substructure – a case study - Soh, Wei Siang; Rashid, Raizal S.M.; Amran, Mugahed; Alengaram, U. Johnson (Elsevier, 2022)
Vehicular collision is one of the leading causes of structural failure and the large impact loading leads to failure of the bridge structure. Therefore, the structural behavior of bridge substructure including the piles is the chief topic in this paper. Numerical finite element analysis (FEA) software ANSYS was used for simulating the FE model. This paper describes a numerical analysis of the pile structural behavior of a bridge substructure under vehicle collision as a case study. The aim of this case study was to evaluate the response of the bridge substructure and soil to impact loading as well as to discuss the interaction between soil and piles. Validation of the model was conducted by comparing the experimental result from pendulum impact test with the numerical result from FEA software. Detailed 3D FE models of the bridge superstructure, substructure, and soil were developed for this purpose. The bridge model was developed on the basis of the verified model’s material detail and contact types. A half-length bridge deck with two piers was supported at the bottom edge. Pile caps and piles were embedded into rectangular soil. Soil springs were also defined to emulate the behavior of soil. An impact force-time history was subjected to the bridge pier; the response of bridge substructure and soil are also discussed. The numerical FE bridge model is able to provide an explanation of the displacement of bridge substructure and soil. Responses of the bridge substructure and soil were primarily concentrated the lateral displacement, vertical displacement, and equivalent stress. This response was investigated in accordance with the length, height, and depth of the bridge structure component. In addition, the soil–pile interaction under vehicular collision was also inspected. On the basis of the obtained results, it can be deduced that the soil is affected by the movement of piles and the soil itself after being subjected to the impact load.